AB0240 ALCOHOL CONSUMPTION AND DEVELOPMENT OF ARTHRITIS AMONG PATIENTS WITH ANTI-CITRULLINATED PEPTIDE ANTIBODIES AND MUSCULOSKELETAL PAIN. (June 2019) - Eloff, Emma; Ziegelasch, Michael; Martinsson, Klara; Cedergren, Jan; Reckner, Åsa; Skogh, Thomas; Karlsson, Louise; Ärlemalm, Andreas; Kastbom, Alf
Abstract : Background: Individuals with anti-citrullinated peptide antibodies (ACPA) and arthralgia are at increased risk of developing rheumatoid arthritis (RA). Predictors of disease development are important within this category of patients in order to improve treatment and follow-up decisions. Although excessive use of alcohol is well-known to cause harmful medical and social consequences, an inverse association between alcohol consumption and RA development has been proposed. Phosphatidylethanol (PEth) has shown to be a reliable biomarker to measure recent (up to four weeks) alcohol consumption with high specificity. Objectives: The aim of this study was to, in relation to other possible clinical and laboratory predictors, pinpoint the association between biochemically determined alcohol consumption and development of arthritis in ACPA-positive individuals with musculoskeletal pain. Methods: The study was performed as part of an observational prospective cohort (TIRx), including 104 ACPA-positive individuals with musculoskeletal pain and maximally one arthritis upon clinical examination. Exclusion criteria were >1 clinical arthritis, previous inflammatory rheumatic disease, and oral or intraarticular corticosteroid treatment within 6 weeks prior to screening. Participants were enrolled between 2010 and 2013 and were carefully followed during 72 months in median (range 23-91). The primary outcome measure was development of arthritis upon clinical examination. In baseline samples, we assessed ACPA levels in serum (2 nd generation cyclic citrullinated peptides (CCP) as antigen), rheumatoid factor (RF), and the presence of shared epitope. PEth 16:0/18:1 was measured by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) in whole blood from baseline, and the results were categorized into three groups: no/low, moderate, or high consumption. Cox regression analyses were performed adjusting for smoking, symptom duration, age, sex, shared epitope, RF, and treatment with disease modifying antirheumatic drugs (DMARDs) and oral glucocorticoids. Results: In TIRx, 82 patients had no swollen joints at inclusion, of whom 39 (48%) developed arthritis during follow-up after median 6 months (range 1-71). Of those, 48 (59%) patients were classified according to PEth values with no/low alcohol consumption, 28 (34%) with moderate consumption and 5 (6%) patients with high alcohol consumption. There was no significant difference in PEth values between patients with one baseline arthritis compared to those without (p=0.09). Neither were there any significant differences in arthritis-free survival across PEth categories versus arthritis development (p=0.64). Unadjusted hazard ratios (HRs) were numerically, but not significantly, increased among moderate (HR 1.22 95% CI 0.63-2.37, p=0.56) and high consumers (HR 1.69 95%CI 0.50-5.68, p=0.40) as compared to those classified as no/low consumers. There was an increased risk of arthritis development regarding RF positivity (adjusted HR 3.13, 95% CI 1.36-7.19, p=0.007) and higher ACPA levels (adjusted HR 1, 001 95% CI 1.000-1.001, p<0.001), respectively. Conclusion: This study does not show a significant association between biochemically assessed recent alcohol consumption and arthritis development in ACPA-positive individuals with musculoskeletal pain. Thus, PEth does not appear to be a clinically useful biomarker to predict disease development in ACPA-positive at-risk populations. Whether it may predict arthritis in a seronegative population remains to be determined. We confirm that RF positivity and ACPA levels associate with arthritis development in an ACPA-positive population. Disclosure of Interests: Emma Eloff: None declared, Michael Ziegelasch Consultant for: AbbVie, MSD, Pfizer, and BK-Medical, Klara Martinsson: None declared, Jan Cedergren: None declared, Åsa Reckner: None declared, Thomas Skogh: None declared, Louise Karlsson: None declared, Andreas Ärlemalm: None declared, Alf Kastbom Consultant for: Roche and Pfizer, Employee of: Sanofi, Speakers bureau: UCB and BMS